![](https://cdn.statically.io/img/www.mathcelebrity.com/community/data/avatars/m/0/1.jpg)
Factor x^2 - 4x - 12 using binomials:
(x + 2)(x - 6)
Therefore, factors are x = -2, x = 6
Factor 12 - 4x - x^2
-(x - 6)(x + 2)
Therefore, factors are x = -2, x = -6
Because they don't have two matching factors, your classmate is incorrect.
ncG1vJloZrCvp2O6osDHnJylnZKntrXFjZympmeTpLquwc2iq7JnpJ2%2Fpq3DrGayp6WneqS4wKyqppmkmnqiv9Keqa2dlGLBqa3TZq9mal1pxW59kWaYp5xdZn9ugNdmr2ZqXZ2utHnToZxmq5Gism6ywJyrqKqjYra0ediorKtlk6GutL%2FMmqueZmRrfnZ7